Applications of the Camera Aura Detection Diagnostic Tool for Psychologist in Handling Cases of Mental Health Disorder Due to Domestic Violence in Surabaya City Area - Her Gumiwang Ariswati; Hari Wisana, I Gede Dewa; Lusiana; Utomo, Bedjo (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
ABSTRACT The Community Service Program is implemented in the form of synergistic collaboration between the Surabaya Ministry of Health Polytechnic and the Surabaya City Health Service and the Kenjeran Community Health Center as partners that are oriented towards community independence, especially the psychologist community in the implementation of the use of the GDV Camera Aura Detection Tool for Psychologists in Treatment. Cases of Mental/Psychological Health Disorders Due to Domestic Violence in the Surabaya City Area. In connection with the increasing number of cases of mental/psychological disorders due to domestic violence in the Surabaya City area, the limited number of personnel and diagnostic tools has resulted in a lack of treatment for these patients, which has an impact on disrupting the health service system for patients. Mental health, which is a mental or psychological disorder, is still a concern for the Indonesian government at this time. In 2018, as many as 282,654 household members or 0.67 percent of the population in Indonesia experienced mental disorders. Meanwhile, mental disorders due to domestic violence in the city of Surabaya in 2015 amounted to 46.42%, in 2016 the percentage was 46.15%, and in 2017 the percentage was 50%. During the Covid 19 pandemic (2020-2021), 355 women experienced psychological violence. This Community Service activity is an application of several studies in accordance with the road map research that has been carried out by the team leader, including regarding analysis of aura detection with an EEG tool in 2016 which proves that the recorded results of the aura detection tool with EEG results in 2 conditions Psychologically there are differences. On Indonesian Journal of Electrical Engineering and Computer Science Vol. 31, No. 1, July 2023, pp. 553 561 ISSN: 2502-4752 (Scopus Q3) by title ”Aura Detection Using Thermal Camera with Convolutional Neural Network Method for Mental Health Diagnosis” The results obtained from this community service activity were the implementation of socialization and assistance regarding psychological condition examinations using aura detection technology for doctors, psychologists and nurses at partner health centers; Psychological conditions were identified in 6 patients, namely 2 were domestic violence cases and 4 were members of the general public.